2016
DOI: 10.1111/jmft.12138
|View full text |Cite
|
Sign up to set email alerts
|

A Content Analysis of Quantitative Research in Journal of Marital and Family Therapy: A 10‐Year Review

Abstract: We examined the trends of quantitative research over the past 10 years in the Journal of Marital and Family Therapy (JMFT). Specifically, within the JMFT, we investigated the types and trends of research design and statistical analysis within the quantitative research that was published in JMFT from 2005 to 2014. We found that while the amount of peer-reviewed articles have increased over time, the percentage of quantitative research has remained constant. We discussed the types and trends of statistical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 272 publications
0
6
0
Order By: Relevance
“…The approach for the study was descriptive in nature. We based our approach to the analysis on other similar analyses in the past (Blumer et al., ; Parker et al., ; Seedall, Holtrop, & Parra‐Cardona, ) to analyze the frequency that topics related to sex therapy or sexual relationships are discussed in peer‐reviewed MFT/Family studies journals. By using a systematic process, a content analysis identifies and analyzes patterns and themes within various types of content using a unique coding process that focuses mostly on identifying characteristics of the content (Bauer, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach for the study was descriptive in nature. We based our approach to the analysis on other similar analyses in the past (Blumer et al., ; Parker et al., ; Seedall, Holtrop, & Parra‐Cardona, ) to analyze the frequency that topics related to sex therapy or sexual relationships are discussed in peer‐reviewed MFT/Family studies journals. By using a systematic process, a content analysis identifies and analyzes patterns and themes within various types of content using a unique coding process that focuses mostly on identifying characteristics of the content (Bauer, ).…”
Section: Methodsmentioning
confidence: 99%
“…We did so to highlight the areas in which there appears to be a lack of integration between the MFT and sex therapy field, such as general sex education and training. In a manner similar to other content analyses (e.g., Blumer, Hertlein, Smith, & Allen, ; Parker, Chang, & Thomas, ), we determined the extent to which sex research is being published and what themes emerged in the topics and analyses of these articles. Lastly, we examined some of the publishing trends of these articles in order to present them in such a way that the strengths and gaps in the literature would be beneficial to future research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the potential utility of GMM to the marriage and family therapy field, in examining complex family processes or therapeutic change, GMM or latent class growth analyses (LCGA, will be described more in depth below) are being underutilized. Parker, Chang, and Thomas (2016) conducted a content analysis of the quantitative research published in the Journal of Marital and Family Therapy (JMFT) from 2005 to 2014, and found that only n = 10 manuscripts had been published in that decade employing multilevel growth modeling (i.e., growth curve modeling, linear growth model, or multilevel growth model). None of those manuscripts employed GMM or LCGA.…”
Section: Growth Mixture Modeling To Assess Differences In Change Acromentioning
confidence: 99%
“…Recent examples of content analysis applied to professional journals include: an examination of two teacher education journals (Rock, Cheek, Sullivan, Jones, Holden & Kang, 2016), one looking at types and trends of research design and statistical analysis in the Journal of Marital and Family Therapy (Parker, Chang, & Thomas, 2016), and one in the Journal of Black Psychology (Cokley, Awosogba, & Taylor, 2014).…”
Section: Introductionmentioning
confidence: 99%